A 7.4-mW 200-MS/s Wideband Spectrum Sensing Digital Baseband Processor for Cognitive Radios - Yu, Tsung-Han; Yang, Chia-Hsiang; Cabric, Danijela; Markovic, Dejan (My University, 2012)
"A digital baseband cognitive radio spectrum sensing processor with 200-kHz resolution over 200-MHz bandwidth is integrated in 1.64 mm in 65-nm(2) CMOS. The processor uses adaptive channel-specific threshold and sensing time to achieve detection probability >= 0.9 and false-alarm probability <= 0.1 for -5-dB SNR and adjacent-band interferers of 30-dB INR within a 50-ms sensing time. The chip power and area are minimized by jointly considering algorithm, architecture, and circuit parameters. The chip dissipates 7.4 mW for a 200-MHz sensing bandwidth, which is a 22x reduction in power per sensing bandwidth compared with prior work."
Keywords: CMOS digital integrated circuits; cognitive radio (CR); power and area minimization; wideband spectrum sensing